Histone H3K27ac separates active from poised enhancers and predicts developmental state - Creyghton, Menno P; Cheng, Albert W; Welstead, G Grant; Kooistra, Tristan; Carey, Bryce W; Steine, Eveline J; Hanna, Jacob; Lodato, Michael A; Frampton, Garrett M; Sharp, Phillip A; Boyer, Laurie A; Young, Richard A; et al. (Proceedings of the National Academy of Sciences - PNAS, 2010)
Developmental programs are controlled by transcription factors and chromatin regulators, which maintain specific gene expression programs through epigenetic modification of the genome. These regulatory events at enhancers contribute to the specific gene expression programs that determine cell state and the potential for differentiation into new cell types. Although enhancer elements are known to be associated with certain histone modifications and transcription factors, the relationship of these modifications to gene expression and developmental state has not been clearly defined. Here we interrogate the epigenetic landscape of enhancer elements in embryonic stem cells and several adult tissues in the mouse. We find that histone H3K27ac distinguishes active enhancers from inactive/poised enhancer elements containing H3K4me1 alone. This indicates that the amount of actively used enhancers is lower than previously anticipated. Furthermore, poised enhancer networks provide clues to unrealized developmental programs. Finally, we show that enhancers are reset during nuclear reprogramming.